Matematika di Era Digital: Antara Kecanggihan Teknologi dan Penurunan Kemampuan Dasar - Siti Maftuhah; Imam Sujarwo (Advances In Education Journal, 2025)
The development of digital technology has changed the way students access and process information in mathematics learning. Although technology provides efficiency in completing tasks, the tendency for over-reliance has resulted in a weakening of basic mathematical skills, particularly numeracy skills and conceptual understanding. This study aims to analyze this phenomenon through a descriptive qualitative approach. The research subjects included 25 eighth-grade students and a mathematics teacher at MTs Nurul Huda Singosari. Data were obtained through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that the use of digital calculators, problem-solving applications, and search engines led to a decline in students' ability to solve problems manually and construct logical solution steps. These findings emphasize the need for pedagogical strategies that balance the use of technology with strengthening fundamental mathematical skills.